PENGARUH SOCIAL MEDIA MARKETING, CITRA MEREK, DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN KOPI KENANGAN - Qamilla Nurul Halimah; Suharyati Suharyati (Jurnal Bina Bangsa Ekonomika, 2024)
The development of the use of technology and social media, helps coffee shop businesses grow and compete. One of them is the Kenangan Coffee shop business. Some important variables that are taken into consideration for consumers in choosing which coffee shop to go to are Instagram social media marketing, brand image, and service quality. The purpose of this study is to determine and analyze the influence of Instagram social media marketing variables, brand image, and service quality on the purchase decision of Kopi Kenangan.This study includes quantitative research and uses questionnaires as primary data. Hypothesis testing was carried out using the Partial Least Square method and using the help of SmartPLS 3.0 software applications. The results of the research obtained are Instagram social media marketing variables have a positive and significant effect on purchase decisions. This shows that uploading content on Instagram social media can influence consumer purchasing decisions. Brand image variables do not have a significant influence on purchasing decisions. Service quality variables have a positive and significant influence on consumer purchasing decisions. This proves that good service from coffee shop employees can influence consumer purchasing decisions